2020
DOI: 10.4103/jehp.jehp_740_19
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education on attachment skills in the promotion of happiness among women with unplanned pregnancy

Abstract: BACKGROUND: Happiness is among the factors that promote mental health in mothers with unplanned pregnancy. The present study aimed to determine the impact of attachment skills training on happiness among women with unplanned pregnancy. MATERIALS AND METHODS: This clinical trial was conducted on 84 women with unplanned pregnancy referred to three prenatal clinics in Shiraz in 2018. The participants were randomly divided into an intervention group and a control group usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These were grouped into the following: whether it measured the effect of pregnancy on the SWB of pregnant women, the effect of SS on the SWB of pregnant women, and whether an intervention or a qualitative approach was used. A total of 13 studies were included in the pregnancy itself (Lips, 1985 ; Drescher et al, 2003 ; Taşdemir et al, 2010 ; Ndombe et al, 2011 ; Aasheim et al, 2014 ; Chang et al, 2014 ; Malhotra et al, 2015 ; Türk et al, 2017 ; Farooq et al, 2018 ; Robinson et al, 2018 ; Ishfaq and Mushtaq, 2019 ; Branecka-Wozniak et al, 2020 ; Tesfa et al, 2020 ), 16 studies in SS (Giblin et al, 1987 ; Stevenson et al, 1999 ; Macleod and Weaver, 2003 ; Elsenbruch et al, 2007 ; Rokach, 2007 ; Emmanuel et al, 2012 ; Ngai and Ngu, 2013 ; Gebuza et al, 2014 ; Goodman et al, 2014 ; Calou et al, 2018 ; Gul et al, 2018 ; Nakamura et al, 2018 ; Pakseresht et al, 2019 ; Yu et al, 2020 ; MoghaddamHosseini et al, 2021 ), three interventions (Corno et al, 2018 ; Nazari et al, 2018 ; Hasanzadeh et al, 2020 ), and two qualitative studies (Cynthia Logsdon et al, 2005 ; Kazemi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These were grouped into the following: whether it measured the effect of pregnancy on the SWB of pregnant women, the effect of SS on the SWB of pregnant women, and whether an intervention or a qualitative approach was used. A total of 13 studies were included in the pregnancy itself (Lips, 1985 ; Drescher et al, 2003 ; Taşdemir et al, 2010 ; Ndombe et al, 2011 ; Aasheim et al, 2014 ; Chang et al, 2014 ; Malhotra et al, 2015 ; Türk et al, 2017 ; Farooq et al, 2018 ; Robinson et al, 2018 ; Ishfaq and Mushtaq, 2019 ; Branecka-Wozniak et al, 2020 ; Tesfa et al, 2020 ), 16 studies in SS (Giblin et al, 1987 ; Stevenson et al, 1999 ; Macleod and Weaver, 2003 ; Elsenbruch et al, 2007 ; Rokach, 2007 ; Emmanuel et al, 2012 ; Ngai and Ngu, 2013 ; Gebuza et al, 2014 ; Goodman et al, 2014 ; Calou et al, 2018 ; Gul et al, 2018 ; Nakamura et al, 2018 ; Pakseresht et al, 2019 ; Yu et al, 2020 ; MoghaddamHosseini et al, 2021 ), three interventions (Corno et al, 2018 ; Nazari et al, 2018 ; Hasanzadeh et al, 2020 ), and two qualitative studies (Cynthia Logsdon et al, 2005 ; Kazemi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fordyce happiness training, focused on self-efficacy, was the subject of research of Nazari et al ( 2018 ), whereas Hasanzadeh et al ( 2020 ) applied attachment training to their study. There was a substantial distinction between the pretest and posttest mean happiness levels of the two groups in both the investigations (Nazari et al, 2018 ; Hasanzadeh et al, 2020 ). The study revealed that without the training, there was a substantial reduction in the happiness median score and an increase in perceived stress ratings at the conclusion of the trial when compared with preintervention data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, happiness has been described as the satisfaction and positive effect on life and a relative absence of negative affect. [ 2 ] Happy people have four constant characteristics: self-esteem, optimism, self-control, and extraversion[ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%